URGENSI PEMBELAJARAN TAFSIR AMALY DALAM PEMBINAAN AKHLAK SISWA DI MA AL URWATUL WUTSQO JOMBANG - Ilfiana; Qurrotul Ainiyah (LP3M IAI Al Urwatul Wutsqo Jombang, 2021)
Islamic education is oriented to the Qur'an. Al-Qur'an is something that must be taught in Islamic education, especially the issue of monotheism and morals in Islam, so to make it easier for students about monotheism and morals in Islam, a medium is needed to achieve goals, and a media is measured by its speed and flexibility as through Learning Amaly's Tafsir to understand how a Muslim should behave towards Allah. The research objective is the Education of Tawheed in the Al-Qur'an Surah Al-Ikhlas in Building Morals to God through learning Amaly Tafsir. This research uses a type of field research (field research) with a qualitative approach that is descriptive in nature, with data collection techniques through interviews, observation, and documentation. Then the data were analyzed using the descriptive qualitative analysis method, namely the collection of descriptive data in the form of words instead of numbers. From the results of the research it was found that tauhid education through learning the interpretation of amaly at MA UW includes planning / preparation both physically and mentally, using various methods including driil methods (2x3 principles), lectures, assignments and questions and answers whose theory concerns how to tawhid to Allah who realized with morals. The guidance that is applied is istiqomah praying before entering class, reading the Koran before learning begins, congregation, istigasah, recitation, school and good deeds. However, there are some students who still often violate so that an educator must be able to lead to good morals with the efforts of teachers of Amaly interpretation in building student morals including: motivating students, guiding students, providing advice, building good habits and giving examples to students.